PENGARUH PEMBERIAN MULTIVITAMIN PADA PAKAN TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN PATIN (Pangasius pangasius) - Ahmad Khabib Ulin Nuha; Andi Rahmad Rahim; Aminin Aminin (Universitas Muhammadiyah Gresik, 2019)
As one of fish commodity, Catfish (Pangasius pangasius) has a very important economic value for the community. The time needed for catfish cultivation tends to be long and the price of feed is high so that it triggers the less optimal production of catfish. One way to maximize good production and with minimized time is by adding multivitamin probiotics to the feed. This research aims to analyze the optimal dose of probiotics to the growth and survival rate of catfish . Method used is Complete Randomized Design Design (CRDD) using 4 treatments of probiotic doses and 3 replicates. The treatments are A Control (0.00 ml/kg), B (10 ml/kg), C (15 ml/kg), and D (20 ml/kg). Absolute weight, absolute length, and survival of catfish are the main variables observed. The data were analyzed by using the analysis of variance and continued with the LSD test (the Least Significant Difference), Ü = 0.05. The optimal dose of probiotics based on the absolute length and absolute weight of catfish is 10 ml/kg and it produces an absolute weight of 5.27 gram and absolute length of 5.76 cm. The optimal daily specific growth rate is at the probiotics dose of 10 ml/kg which is 2.302.55%/day. The highest survival rate for catfish is 100% at probiotic doses of 0.000 ml/kg, 10 ml/kg and 15 ml/kg. The range of water quality is in the temperature of 27.5 – 28,90C, pH 6.79 - 7.88, DO 6.4 - 7.9 ppm, and ammonia 0 ppm.